LATE EVALUATION OF PATIENTS UNDERGOING MANIPULATION OF THE KNEE AFTER TOTAL ARTHROPLASTY - DE SOUSA FILHO,PEDRO GUILME TEIXEIRA (2017)
ABSTRACT Objective: We compared gains in range of motion in patients who underwent manipulation within 12 weeks of total knee arthroplasty (TKA) and after this period. We also evaluated maintenance of the arc obtained from knee manipulation in late follow-up, along with factors associated with poorer outcomes. Method: The study was divided into two groups according to the time after TKA; the surgeries took place between January 2008 and December 2014. Results: When comparing the range of motion between early and late manipulations, the group that underwent manipulation within 12 weeks of the TKA exhibited better outcomes, but these were not statistically significant. We observed that 14.3% of cases retained the same range attained at the time of manipulation. In late evaluation after manipulation, 47.7% of the sample had a range of less than 90 degrees. The significant risk factors for recurrence of knee stiffness in the long term are poor range of motion before TKA and before manipulation, female sex, and secondary arthritis. Conclusion: Women previously diagnosed with secondary osteoarthritis and poor range of motion before TKA or manipulation are at higher risk for late stiffness. Level of Evidence III, Retrospective Comparative Study.